Vizuelni evocirani potencijali – sadašnji koncepti i buduće perspektive - Jančić, Jasna; Ivančević, Nikola; Nikolić, Blažo; Popović, Mirjana; Martinović, Žarko; Stevanović, Dejan; Grbić, Marina; Djurić, Vesna; Samardžić, Janko (Vojnosanitetski pregled, 2020)
No abstract for the review paper